Испанский текст в поэзии Александра Анашевича - Kristina Vorontsova (Acta Universitatis Wratislaviensis. Slavica Wratislaviensia)
This paper analyzes the origins and key features of Spanish influence on Russian culture and literature, particularly evident in the poetry of Alexander Anashevich from the 1990s to the 2010s. The author places significant emphasis on the urban context of Madrid, a city characterized by its profound emotional depth, physicality, erotic motifs, and dreamlike qualities. Additionally, Madrid serves as a logical counterpoint to St Petersburg, often considered the most literature-rich city in Russia, creating a geo-cultural “South–North” dichotomy. In this artistic exploration, Spain as a whole serves as a prototype for a universe that encompasses both heavenly and hellish elements within its creative sphere. In summary, Anashevich presents an idealistic landscape that is most suitable for erotic lyrics while also serving as a space for transgressive themes.